Effects of occupant behavior on the energy performance of dwellings: a sensitivity analysis - Ulukavak Harputlugil, Gülsu; Bedir, Merve (A+BE | Architecture and the Built Environment, 2018)
Chapter 3 is a sensitivity analysis conducted using the actual heating behavior data of occupants in the OTB sample. The aim was to model heating behavior and heating energy consumption using Markov chains and Monte Carlo methods. Secondly we wanted to evaluate the robustness of energy consumption of a dwelling to heating behaviors such as thermostat, radiator and ventilation control, as well as presence. The results of this Chapter were compared to Guerra Santin’s work (2010), which analyzes the same data using correlation and regression analyses. This Chapter deals with the Research Question I of this thesis: “Q I. What is the sensitivity of a dwelling’s heating energy consumption to occupant behavior?" The sub-questions are: 1. What are the existing models developed for the occupant behavior and energy performance relationship? and how different are the results of these models in terms of calculating the influence of occupant behavior on energy performance? 2. How can behavior be modelled in order to assess the robustness of the energy performance in dwellings to occupant behavior? 3. What is the weight of each behavioral aspect in terms of its influence on energy consumption?” The research reported in this Chapter was a collaborative work between Harputlugil and Bedir. The data was collected by a questionnaire prepared by Guerra Santin and Bedir, using OTB’s means of data collection. Data organization and initial statistical analysis was done by Bedir, simulations were conducted by Harputlugil and Bedir together, and finally the evalutation of outputs were done by the same authors. The co-author (G. Harputlugil) has given permission to include this paper in this thesis.